H₂O₂-modified TiO₂ : Synthesis, Deposition, Properties, and Applications - Gibas, Anna (TiO₂ modyfikowany H₂O₂ : synteza, osadzanie, właściwości i zastosowania, 2025)
The presented dissertation consists of a cycle of five scientific articles aiming at developing the synthesis and deposition of H2O2-modified TiO2, which can be applied to the degradation of organic pollutants and bacteria under visible light and in the dark. Selected hydrogen peroxide-based modification is a dopant-free strategy introducing peroxo and superoxo groups which narrows the bandgap energy. The important aspect of the thesis was designing a low-pressure cold spray process for the formation of coatings that maintain the initial characteristics of feedstock materials. The application of feedstock in the form of powder, suspension and aerosolised suspension aimed at investigating the control over the preservation of oxygen-rich groups. The obtained H2O2-modified TiO2 coatings are the results of a synergistic combination of sol-gel synthesis which imparted physicochemical characteristics providing catalytic activity and low-pressure cold spraying that caused thermal drying and offered large-scale technique to produce coatings.
Keywords: TiO₂; oxygen-rich groups; sol-gel synthesis; low-pressure cold spray; suspension spraying